The Role of Local Culture on The Effect of Leader Member Exchange on Employee Performance at Village Offices in Abiansemal District - Ida Ayu Ketut Sri Wiratih; I Gede Putu Kawiana; Putu Herny Susanti (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
Public administration currently refers to the professionalism of the performance of government officials in public services One of the agencies formed by the local government is the Village Office. The purpose of this study was to analyze the role of local culture in the relationship of leader member exchange to the performance of employees at the Village Office in Abiansemal District. The research is causal in nature to provide an explanation and understanding of the relationship between the leader member exchange variable, local culture and employee performance variables. The research population was all employees of the Village Office in Abiansemal District, totaling 269 employees. Questionnaires that have been tested for validity and reliability were given to 73 respondents. Methods of data collection by observation, interviews, documentation, literature and questionnaires. The method of determining the sample with a saturated sample and the method of analysis using descriptive analysis and inferential analysis with Partial Least Square (PLS) analysis. The results show that the leader member exchange variable has an effectsignificanton employee performance, local culture has an effect positive and significant on employee performance.Local culture is not able to moderate the influenceleader member exchangeon employee performance but tends to be a predictor variable because it has positive but not significant results.